Learning from the RSPT mistakes: is reform still possible?. Issue 1 (2nd January 2016) - Kellow, Aynsley
ABSTRACT: The political ramifications of the failed Resources Super Profit Tax have been widely documented, yet the causes of this political failure are more contested. Many accounts highlight the discursive power of business and the effectiveness of their campaign against the mining tax. Effective business activism certainly played its part, but this article argues that strategic failings on the part of government also influenced the outcome. This article highlights how the Labor government's failure to consult, to understand the political implications of federalism and above all its impact on the industry in the hope that future policymakers will learn from the mistakes of the mining tax debacle.